Comparison of Hepcidin Level, Blood Parameters and Inflammatory Markers in High Flux Hemodialysis and Hemodiafiltration Patients - MY Naji Al-Atbee; H Sami Tuama; R Abdulwahid Gatee; MM Salih Hasan; S Ali Salman; Gh Hasan Mahmood (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Healthy kidneys filter wastes of various molecular masses (up to 40-60 kDa). Traditional hemodialysis only removes low-molecular-weight molecules (500 Da), not middle-weight substances (>500 Da). Therefore, most of these compounds remain as expected uremic toxins. Therefore, this study aims to determine the association of Hepcidin and anemia with inflammatory markers in dialysis cases on high flux hemodialysis (HD) compared with hemodiafiltration (HDF). Methods: This cross-sectional study was conducted on 203 patients in the age range of 20-70 years old with end-stage kidney disease who were undergoing hemodialysis using high flux and hemodiafiltration methods. Venous blood samples were taken without anticoagulation and ferritin, CRP and hepcidin levels were analyzed and compared. Findings: This study involved 203 cases with end-stage renal disease, with 103 in the HD group and 100 in the HDF group. The mean age of the cases was 49.5±15.5 years. Among the patients in the HD group, 79.9% had hypertension, while only 23% of the patients in the HDF group had hypertension. Additionally, 35.9% of the cases in the HD group had diabetes mellitus (DM), while 75% of the cases in the HDF group had DM. There were significant differences between the mean number of white blood cells (8.27±7.95 vs. 6.20±4.14), CRP (13.88±17.45 vs. 6.48±10.40) and hepcidin (2981.47±2325.38 vs. 1010.45±1136.18) between the groups (p<0.05). Conclusion: The results of this study showed that individuals receiving HDF have low-grade inflammation, less anemia, and a superior response to erythropoietin. Therefore, for patients with elevated inflammatory markers, the HDF dialysis modality is suggested.